Hygrothermal chamber aging effect on mechanical behavior and morphology of glass fiber-epoxy-nanoclay composites. (6th January 2020) - Shettar, Manjunath; Kini, U Achutha; Sharma, Sathyashankara; Hiremath, Pavan; M C, Gowrishankar
Abstract: This work examines the impact of artificial aging on tensile and flexural behavior of epoxy-nanoclay composites (ENCs) and glass fiber-epoxy-nanoclay composites (GFENCs) in the hygrothermal chamber. Epoxy-nanoclay composites made by a general-casting technique, and GFENCs are made by hand layup technique. The specimens are aged in the hygrothermal chamber for 180 days at 40 °C with 60% RH. The results revealed that an increase in nanoclay and glass fiber weight percentage enhanced the mechanical behavior of GFENCs. The aging of the sample has a negative influence on the composite materials. But, the increase in nanoclay and glass fiber weight percentage has diminished the impact of aging on the mechanical behavior of composites. SEM micrographs revealed the reason for the failure and influence of aging conditions.